Review of Vocational Education in England: The Wolf Report Analysis, Recommendations and Government Response - Steedman, Hilary [Verfasser] (My University, 2011)
"Commissioned to "consider how [to] improve vocational education for 14-19 year olds and thereby promote successful progression into the labour market and into higher level education and training routes" (Written Ministerial Statement 2010), the Wolf Review of Vocational Education was tasked with analysing the current state of VET in England and making recommendations as to its future development. Presented in the resulting Wolf Report, the Review's analysis and recommendations are best understood as falling under the following headings: outcomes of the 14-16 (compulsory) stage of education; the study of mathematics and English 14-19; outcomes of 16-19 (post-compulsory) provision for students enrolled on vocational courses; and the pro-vision of apprenticeship places for 16-19 year olds. In this article, important results of the analysis and central recommendations of the Wolf Report, dealing, among others with questions of funding, management and assessment in English VET, are summarised and discussed along with the government's response to the Report." (Autorenreferat, BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; I 2.2.1 Westeuropa; Berufsbildung; Arbeitsmarkt; Jugendlicher; Bildungsniveau; Bildungspolitik; England